Angiotensin II is required to induce exaggerated salt sensitivity in Dahl rats exposed to maternal separation. Issue 5 (21st May 2015) - Loria, Analia S.; Pollock, David M.; Pollock, Jennifer S.
Abstract: We previously reported that maternal separation, rat model of early life stress, enhances pressor responses to acute and chronic stressors. The aims of this study were to determine whether Dahl salt‐sensitive (DS) rats subjected to maternal separation (MatSep‐DS) as compared to normally reared DS (Ctl‐DS) rats show exaggerated blood pressure responses to acute behavioral stressors, such as restraint stress or air jet stress (AJS), or, hypertensive stimuli including chronic high‐salt diet (4% NaCl) and angiotensin II (AngII) infusion (200 ng/Kg/min) during 1 week. MatSep was performed in male DS rats for 3 h/day from postnatal days 2–14. At 8 weeks of age, rats were implanted with telemetry transmitters and allowed to recover. Mean arterial pressure (MAP) was not different between MatSep‐DS and Ctl‐DS rats at baseline (120 ± 2 mmHg vs. 118 ± 1 mmHg, n = 4–8). Blood pressure responses during AJS and restraint stress were not different between MatSep‐DS and Ctl‐DS at 3 min. However, blood pressure recovery from AJS was significantly impaired in MatSep‐DS rats compared to Ctl‐DS rats ( P < 0.05). 3‐h stress‐induced similar responses in MatSep and Ctl‐DS rats. Chronic blood pressure responses to AngII infusion in rats fed a high‐salt diet displayed enhanced MAP in MatSep‐DS when compared with Ctl‐DS rats (167 ± 5 mmHg vs. 152 ± 2 mmHg, pinteraction <0.05). However, MAP increased similarly in both groups in response to AngII infusion or high‐salt diet separately. Renal parameters such as proteinuria, urine flow rate, and urine electrolytes were not different between groups in response to each treatment. In summary, salt sensitivity induces exaggerated blood pressor responses only in presence of AngII due to early life stress. Abstract : The aims of this study were to determine whether Dahl salt‐sensitive rats subjected to maternal separation (MatSep‐DS) as compared to normally‐reared DS (Ctl‐DS) rats elicit exaggerated blood pressure responses to acute behavioral stressors or chronic hypertensive stimuli. We found that early life stress in a genetic rat model of salt‐sensitivity induces exaggerated chronic blood pressor responses only in presence of AngII.